MODELING THE OPTICAL SPECTRUM OF ROMANO‘S STAR IN MINIMUM BRIGHTNESS - Maryeva, O.; Abolmasov, P. (Одеські астрономічні публікації, 2010)
V532, known as Romano‘s star, is an interesting variable star located in the M33 galaxy. We study its spectral variability and the optical spectrum in minimum brightness. Using the non-LTE radiative transfer code CMFGEN we model the structure of its expanding atmosphere and stellar wind. The calculations show that all the observed properties of the object are well described by a late WN star model with high hydrogen abundance. We find that the luminosity of the object is L = (0.8 ± 0.2) · 106Lsun, its mass loss rate is (4.5 ± 0.5) · 10-5Msun/year and the terminal wind velocity is 400±100 km/s. We also find that H/He is 1.3 ÷ 1.8.